Cardio-respiratory monitoring in archery using a smart textile based on flexible fiber bragg grating sensors - Lo Presti, D.; Romano, C.; Massaroni, C.; D`Abbraccio, J.; Massari, L.; Caponero, A. M.; Oddo, M. C.; Formica, D.; Schena, E. (Sensors, 2019)
In precision sports, the control of breathing and heart rate is crucial to help the body to remain stable in the shooting position. To improve stability, archers try to adopt similar breathing patterns and to have a low heartbeat during each shot. We proposed an easy-to-use and unobtrusive smart textile (ST) which is able to detect chest wall excursions due to breathing and heart beating. The sensing part is based on two FBGs housed into a soft polymer matrix to optimize the adherence to the chest wall and the system robustness. The ST was assessed on volunteers to figure out its performance in the estimation of respiratory frequency (fR) and heart rate (HR). Then, the system was tested on two archers during four shooting sessions. This is the first study to monitor cardio-respiratory activity on archers during shooting. The good performance of the ST is supported by the low mean absolute percentage error for fR and HR estimation (≤1.97% and ≤5.74%, respectively), calculated with respect to reference signals (flow sensor for fR, photopletismography sensor for HR). Moreover, results showed the capability of the ST to estimate fR and HR during different phases of shooting action. The promising results motivate future investigations to speculate about the influence of fR and HR on archers’ performance.